If electric cars are the answer, what was the question?. Issue 1 (7th January 2019) - Jones, Sarah J
Abstract: Introduction: Roads facilitate trade, development and communication, as well as spread illness and disease, but since mass car use began, the disbenefits, including injuries, pollution and physical inactivity have been significantly magnified. Electric cars are now being seen by many as the solution to the problems associated with internal combustion engine cars. Sources of data: This article reviews existing literature to determine the extent to which a switch to electrification can solve many of the problems that cars have wrought. Areas of agreement: It concludes that there may be some benefits in rural areas, where public transport is poor. Areas of controversy: However, it also argues that even in rural areas it may be better to invest in public transport for many, rather than electric car infrastructure for some. It is clear that even for air quality, where electric cars are suggested to offer benefits these are unlikely to be as great as has been suggested. Overall, the negative health consequences of electric cars seem likely to be at least those of internal combustion engine cars.